How can Awareness Enhance Leadership Effectiveness in Organizations - Nanang Qosim Yusuf; Dewi Umronih Yusuf (Bina Nusantara University, 2025)
Leadership plays a strategic role in determining organizational effectiveness. Amid increasingly complex and dynamic organizational environments, awareness leadership has emerged as a contemporary leadership approach that emphasizes self-awareness, empathy, ethical consciousness, and meaningfulness in leadership practices. This study aims to examine the extent to which awareness leadership contributes to organizational effectiveness, particularly in fostering a healthy, productive, and sustainable work culture. A Systematic Literature Review (SLR) method was employed to synthesize and analyze relevant peer-reviewed studies published in reputable international journals.The findings indicate that awareness leadership has a significant and positive influence on organizational effectiveness through several interrelated mechanisms. First, it enhances leaders’ self-awareness regarding organizational vision, values, and strategic goals, enabling more reflective, ethical, and aligned decision-making. Second, awareness leadership strengthens interpersonal relationships by promoting empathy, authentic communication, trust, and collaboration, which in turn improve employee engagement, psychological safety, and organizational commitment. Third, this leadership approach facilitates the development of an adaptive, inclusive, and sustainability-oriented organizational culture that supports continuous learning, innovation, and long-term resilience. the review also reveals that empirical research on awareness leadership remains limited, with a predominant focus on conceptual and qualitative studies. This highlights the need for future research employing quantitative and mixed-method approaches to strengthen empirical validation and explore cross-cultural and sectoral variations. Overall, awareness leadership represents a promising paradigm for enhancing organizational effectiveness through human-centered, values-driven, and sustainable leadership practices.